1992
DOI: 10.3171/jns.1992.77.4.0545
|View full text |Cite
|
Sign up to set email alerts
|

Intracavitary brachytherapy of cystic craniopharyngiomas

Abstract: Visual function, endocrinological status, and radiological outcome are reported in 31 patients harboring a cystic craniopharyngioma, who underwent 35 intracavitary brachytherapy procedures with yttrium-90. In 26 of these patients intracavitary brachytherapy was the primary treatment. The follow-up period ranged from 2 to 80 months (41 +/- 22 months, mean +/- standard deviation). Five patients died from tumor-related causes. Endocrine recovery was modest. Prior to brachytherapy, visual acuity was diminished in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1
7

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(53 citation statements)
references
References 33 publications
2
43
1
7
Order By: Relevance
“…Others advocate intracavitary treatments for cystic tumors including irradiation with beta-emitting radioisotopes (phophorus-32 or yttrium-90) 5,33,38,60,61,87,89 or administration of the chemotherapeutic agent bleomycin, an antineoplastic antibiotic that interrupts DNA synthesis. 32,37,54,82 Many reported series utilizing intracavitary therapies are made up of small numbers of patients and usually include small-to moderate-sized, monocystic tumors, not multicystic giant forms.…”
Section: Treatment Options For Giant Craniopharyngiomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Others advocate intracavitary treatments for cystic tumors including irradiation with beta-emitting radioisotopes (phophorus-32 or yttrium-90) 5,33,38,60,61,87,89 or administration of the chemotherapeutic agent bleomycin, an antineoplastic antibiotic that interrupts DNA synthesis. 32,37,54,82 Many reported series utilizing intracavitary therapies are made up of small numbers of patients and usually include small-to moderate-sized, monocystic tumors, not multicystic giant forms.…”
Section: Treatment Options For Giant Craniopharyngiomasmentioning
confidence: 99%
“…Nevertheless, the long-term consequences of using these minimally invasive methods as primary treatment are unclear, and they are not without complications. 37,38,47,54,61,71,87 In terms of radical resection of giant craniopharyngiomas, some authors prefer anterior-to-posterior trajectories, including bilateral subfrontal 2,4 or frontobasal interhemispheric approaches. 76 Others have reported success with lateral trajectories, including pterional 95 and petrosal (presigmoid transtentorial) approaches, the latter specifically for retrochiasmatic tumors.…”
Section: Treatment Options For Giant Craniopharyngiomasmentioning
confidence: 99%
“…19 A number of studies have assessed this modality since then. 4,5,7,11,17,21,22,27,28 By and large, these studies have shown good cyst control with 1 or more instillations of P32 or yttrium-90. Almost all of these studies (including one from our institution) included patients who underwent multiple modalities of therapy, including varying degrees of resection and EBR.…”
Section: Discussionmentioning
confidence: 86%
“…Numerous studies have been published on its techniques, indications, and efficacy. 4,5,7,11,12,17,21,[26][27][28] In most studies, brachytherapy is combined with EBR. Previously, we attempted to treat predominantly cystic craniopharyngiomas with brachytherapy alone, withholding external radiation.…”
Section: Efficacy Of Phosphorus-32 Brachytherapy Without External-beamentioning
confidence: 99%
See 1 more Smart Citation